Factors of Crew Turnover Intention Influence on the Performance of Shipping Industry: An Empirical Study - Fin, Her; Harito, Christian (International Review of Management and Marketing, 2025)
The purpose of this paper is to determine the factors that influence crew’s turnover intention in the shipping industry. This research used 222 respondents who worked in the shipping industry as a sample. Data was collected using a questionnaire instrument, and the data was processed using the SEM- PLS technique. Companies can use practical implications-Finding from this research to develop strategies and policies related to employee turnover, more specific to ship crew’s turnover. The analysis’s results show that turnover Intention in the shipping industry is influenced by two factors: job satisfaction and organizational commitment. Research on turnover intention in the shipping industry is still very limited, especially with shipping industry objects in Indonesia. It highlights the significant impact of turnover intention on organizational performance, particularly in shipping companies, where high turnover leads to financial losses and operational disruptions. The study contributes to the limited existing literature on turnover intention in the Indonesian shipping sector.